Identification of peptides reflecting the storage of UHT milk by MALDI-TOF-MS peptide profiling. - Dalabasmaz, Sevim; Dittrich, Daniel; Kellner, Ina; Drewello, Thomas; Pischetsrieder, Monika (Journal of Proteomics, 2019)
Proteolysis during the storage of UHT milk is associated with major technological problems, particularly bitter off-flavors and age gelation limiting the shelf life of milk. In this study, untargeted peptide profiling by MALDITOF- MS identified peptides that were formed by proteolysis and reflected the storage of UHT milk. Analysis of nine different commercial UHT samples recorded peptide profiles during and at the end of their shelf life. Relative quantification and sequencing of the peptides revealed that the concentrations of 22 peptides increased significantly during the storage of UHT milk due to the activity of endogenous milk proteases and microbial proteases as well as other unidentified proteolytic mechanisms. Based on highly discriminative AUC values from receiver operator characteristic (ROC) curve analysis, we selected ten peptides as marker candidates. Among those, the peptide β-casein192–206 (m/z 1668.9) was the most suitable marker differentiating expired-UHT from regular-UHT samples with 100% accuracy. Additionally, β-casein191–206 (m/z 1782.0) showed 100% specificity and β-casein139–161 (m/z 2696.4) 100% sensitivity. Thus, β-casein192–206, either by itself or in combination with β-casein191–206 and β-casein139–161, presents a reliable marker to monitor the storage of UHT milk based on proteolytic mechanisms.
Keywords: Peptide profiling; milk proteases; storage; UHT milk; MALDI-TOF-MS

Influence of Software Settings on the Identification Rate, Quantification Results, and Reproducibility in Profiling Post-Translational Modifications by Microflow Liquid Chromatography-Ion Mobility-Quadrupole Time-Of-Flight Analysis Using PEAKS Software - Mauser, Andreas; Gensberger-Reigl, Sabrina; Dalabasmaz, Sevim; Schichtl, Theresa Maria; Dittrich, Daniel; Pischetsrieder, Monika (Journal of Proteome Research, 2024)
The influence of data evaluation parameters on qualitative and quantitative results of untargeted shotgun profiling of enzymatic and nonenzymatic post-translational modifications (PTMs) was investigated in a model of bovine whey protein α-lactalbumin heated with lactose. Based on the same raw data, individual adjustments to the protein database and enzyme settings of PEAKS studio software increased the identification rate from 27 unmodified peptides to 48 and from 322 peptides in total to 535. The qualitative and quantitative reproducibility was also assessed based on 18 measurements of one sample across three batches. A total of 570 peptides were detected. While 89 peptides were identified in all measurements, the majority of peptides (161) were detected only once and mostly based on nonindicative spectra. The reproducibility of label-free quantification (LFQ) in six measurements of the same sample was similar after processing the data by either the PTM algorithm or the LFQ algorithm. In both cases, about one-third of the peptides showed a coefficient of variation of above 20%. However, the LFQ algorithm increased the number of quantified peptides from 75 to 179. Data are available at the PRIDE Archive with the data set identifier PXD050363.
CRIS-Team Scopus Importer:2024-09-27
Keywords: data evaluation; microLC−IM-QTOF; PTM profiling; reproducibility; untargeted proteomics

Profiling of multiphosphorylated peptides in kefir and their release during simulated gastrointestinal digestion - Savastano, Maria Luisa; Liu, Yufang; Ebner, Jennifer; Dittrich, Daniel; Haus, Sabrina; Gensberger-Reigl, Sabrina; Pischetsrieder, Monika (ACS Omega, 2019)
Casein phosphopeptides are multiphosphorylated milk peptides, which can have anticariogenic activity and improve mineral absorption by binding bivalent metal ions. The present study investigated phosphopeptides in kefir, because fermentation may lead to their enhanced release from milk proteins. After selective enrichment by hydroxyapatite extraction, phosphopeptides and their phosphorylation degree were identified by MALDI-TOF-MS before and after enzymatic dephosphorylation. Peptide structures were determined by UHPLC–ESI–MS/MS revealing 27 phosphopeptides in kefir, including nine peptides containing the motif pSpSpSEE, which binds minerals most efficiently. The majority (18) of phosphopeptides derived from β-casein, but only three from the most abundant milk protein αs1-casein. After simulated gastrointestinal digestion, MALDI-TOF-MS analysis detected eight putative phosphopeptides in kefir; four of which were assigned by UHPLC–ESI–MS/MS to αs2-casein124-133, αs2-casein137-146, β-casein30-40, and κ-casein147-161. These results indicate that kefir is a good dietary source of multiphosphorylated peptide
Keywords: casein phosphopeptides; gastrointestinal digestion; kefir; MALDI-TOF-MS; pSpSpSEE; UHPLC–ESI–MS/MS

Untargeted Proteomics-Based Profiling for the Identification of Novel Processing-Induced Protein Modifications in Milk - Meltretter, Jasmin; Wüst, Johannes; Dittrich, Daniel; Lach, Johannes; Ludwig, Jonas; Eichler, Jutta; Pischetsrieder, Monika (Journal of Proteome Research, 2020)
Nonenzymatic post-translational protein modifications (nePTMs) affect the nutritional, physiological, and technological properties of proteins in food and in vivo. In contrast to the usual targeted analyses, the present study determined nePTMs in processed milk in a truly untargeted proteomic approach. Thus, it was possible to determine to which extent known nePTM structures explain protein modifications in processed milk and to detect and identify novel products. The method combined ultrahigh-performance liquid chromatography coupled to electrospray ionization tandem mass spectrometry with bioinformatic data analysis by the software XCMS. The nePTMs detected by untargeted profiling of a β-lactoglobulin-lactose model were incorporated in a sensitive scheduled multiple reaction monitoring method to analyze these modifications in milk samples and to monitor their reaction kinetics during thermal treatment. Additionally, we identified the structures of unknown modifications. Lactosylation, carboxymethylation, formylation of lysine and N-terminus, glycation of arginine, oxidation of methionine, tryptophan, and cysteine, oxidative deamination of N-terminus, and deamidation of asparagine and glutamine were the most important reactions of β-lactoglobulin during milk processing. The isomerization of aspartic acid was observed for the first time in milk products, and N-terminal 4-imidazolidinone was identified as a novel nePTM.
CRIS-Team Scopus Importer:2020-02-18
Keywords: mass spectrometry; processed milk; protein modifications; untargeted profiling; β-lactoglobulin